2020
DOI: 10.1073/pnas.2006890117
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of a key ligand-H-bond network drives dissociative properties in vamorolone for Duchenne muscular dystrophy treatment

Abstract: Duchenne muscular dystrophy is a genetic disorder that shows chronic and progressive damage to skeletal and cardiac muscle leading to premature death. Antiinflammatory corticosteroids targeting the glucocorticoid receptor (GR) are the current standard of care but drive adverse side effects such as deleterious bone loss. Through subtle modification to a steroidal backbone, a recently developed drug, vamorolone, appears to preserve beneficial efficacy but with significantly reduced side effects. We use combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 59 publications
4
34
0
Order By: Relevance
“…Oral administration of vamorolone at all doses tested was safe and well tolerated over the 24-week treatment period. Participants in the 2 higher dose groups (2.0 and 6.0 mg/kg/day) generally showed clinical improvement of motor outcomes, with suggestion of dose-related improvements in all motor outcomes tested [2,14]. However, the 24-week trial period did not allow for adequate evaluation of adverse effects associated with longer-term chronic corticosteroid exposure in children.…”
Section: Plos Medicinementioning
confidence: 94%
See 2 more Smart Citations
“…Oral administration of vamorolone at all doses tested was safe and well tolerated over the 24-week treatment period. Participants in the 2 higher dose groups (2.0 and 6.0 mg/kg/day) generally showed clinical improvement of motor outcomes, with suggestion of dose-related improvements in all motor outcomes tested [2,14]. However, the 24-week trial period did not allow for adequate evaluation of adverse effects associated with longer-term chronic corticosteroid exposure in children.…”
Section: Plos Medicinementioning
confidence: 94%
“…Vamorolone is an anti-inflammatory steroidal drug that differs from all 33 drugs in the corticosteroid class by lacking an 11-carbon oxygen group (hydroxyl or carbonyl) that is 1 of 5 molecular contact sites with the glucocorticoid receptor [1,2]. In vitro pharmacology and preclinical in vivo studies have shown that vamorolone retains the anti-inflammatory activity of steroid drugs, while lacking the adverse effects (AEs) associated with these drugs (stunting of growth, bone morbidities, muscle atrophy) in these models [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, controversy remains about the extent of GRdim dimer formation, as some partial impairment was reported 17,18 . Nevertheless, we have also demonstrated that full-length GR dimerization can be mostly abrogated via mutations in both the DBD and LBD domains, known as the GRmon 15,19,20 , and when activated by hormone, GRwt exhibits no detectable monomers in the nuclear population 15,21 . Furthermore, receptor binding on an activated GRE in live cells induces higher quaternary structures, suggesting that tetramers may be the final active form of GR 19 .…”
mentioning
confidence: 94%
“…The reconstructed ancestral GR LBD (AncGR2 LBD) has been successfully used to study GR because it reliably recapitulates GR ligand binding, transcriptional responses, and allosteric regulation(Bridgham et al, 2009; Kohn et al, 2012; Liu et al, 2020; Liu et al, 2019; Weikum et al, 2017b). The ancestral GR2 ligand binding domain significantly improves protein expression and stability and shares 79% sequence identity with human GR LBD (Figure S1A).…”
Section: Resultsmentioning
confidence: 99%